STRATEGI PEMASARAN AYAM GEPREK DJENG SITI PALEMBANG BERBASIS MATRIKS SWOT DAN QPSM - Widya Permata Sari; Heri Setiawan (Jurnal Ilmiah Dinamika Teknik, 2018)
SME’s Ayam Geprek Djeng Siti is a micro scale industry engaged in the food and beverage enterprise, which targets the low to middle-class population. Based on the market observation of SME’s Ayam Geprek Djeng Siti, it showed that the existing marketing strategy is not befitting with the current marketing trend, thus causing low level of marketing strategy and revenue achieved. The productivity level of its current sales is only as much as 1,39. Therefore, in order to formulate a better marketing strategy, SWOT matrix is essential as a means to determine the strength, weakness, opportunity and threat faced by the SME’s. In addition, the QSPM matrix is also necessary to objectively evaluate the alternative strategic options based on the previously identified internal and external key success factors. For these reasons, SME’s Ayam Geprek Djeng Siti has developed a number of improved strategies, such as promotion via social media (Instagram), working together with gojek, make a brand, customer service, and improving the food packaging. The implementation of these strategies has increased both the productivity and revenue levels by 6% and Rp 368.000,00 per day respectively, with the total profit of Rp 134.467,00 per day. Although the increment level is not dramatic since these strategies have only been implemented for one month, the consistent development and efforts of SME’s Ayam Geprek Djeng Siti will definitely continue to improve the productivity level in the future. Keywords: Marketing Strategy, Productivity, SWOT Matrix, QSPM Matrix